Interaction between Fe66Cr10Nb5B19 metallic glass and aluminum during spark plasma sintering - Dudina, Dina V.; Bokhonov, Boris B.; Batraev, Igor S.; Amirastanov, Yusif N.; Ukhina, Arina V.; Kuchumova, Ivanna D.; Legan, Mikhail A.; Novoselov, Aleksey N.; Gerasimov, Konstantin B.; Bataev, Ivan A.; Georgarakis, Konstantinos; Koga, Guilherme Yuuki; et al. (Elsevier, 2020)
In the area of metal matrix composites, novel reinforcing options are currently being evaluated. Particles of amorphous alloys present an interesting possibility to reinforce soft metals. In the present work, the interaction between Fe66Cr10Nb5B19 metallic glass and aluminum during spark plasma sintering (SPS) was studied for the first time. In order to trace the phase and microstructural changes upon sintering, mixtures containing 20 vol% and 50 vol% of metallic glass were subjected to SPS at 500–570 °C. After SPS at 500 °C, no reaction layer between the metallic glass particles and aluminum was observed. After SPS at 570 °C, a reaction layer containing Fe2Al5 and FeAl3 formed around the Fe-based cores. The Vickers hardness of composites obtained from mixtures containing 20 vol% Fe66Cr10Nb5B19 at 540 °C was 75 HV and increased to 280 HV after sintering at 570 °C due to the formation of thicker reaction layers at the interface. The hardness of the composite sintered from the mixture containing 20 vol% Fe66Cr10Nb5B19 at 570 °C was between the values predicted by Reuss and Voigt models. Comparison of results of SPS of the powder mixtures with those of SPS of a pre-compacted pellet and electric current-free annealing suggests that local heating at the interface caused by interfacial resistance may be an important factor influencing the reaction advancement at the interface and the formation of Al-containing intermetallics
Keywords: Hardness; Scanning electron microscopy; Microstructure; Sintering; Metal matrix composites